Poroelastic Modeling of a Heterogeneous Geologic Medium: A Case Study from Kanto Basin in Japan. Issue 3 (13th January 2021) - Joshi, Ajit; Aichi, Masaatsu; Tokunaga, Tomochika
Abstract: Vertical geological heterogeneity, such as clay content and grain size variation, may affect land subsidence caused by groundwater extraction. In order to test this hypothesis, one‐dimensional pore‐water mass balance and force balance equations of a water‐saturated poroelastic medium were solved under different heterogeneous geological conditions. Results showed that clay content and grain size variation in sandstone could affect subsidence rates by up to an order of magnitude due to the changes in stiffness and permeability of the medium, indicating the importance of small‐scale heterogeneity in subsidence simulation studies. Predicted values of subsidence were in good agreement with field measurements for two sites in the Kanto groundwater basin in Japan, showing the applicability of the model to other groundwater basins with clay‐rich aquifers.